Motivation Creation in Home Economics and Technology Instructional Learning by Using Tokens Economy in Elementary Level 3 at Ramkhamhaeng University Demonstration School (Elementary level) - Srihawong, Sriprapa (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
The objectives of this research were: 1) to study the effect of motivation creation via applying a reward program in home economics and technology education utilizing a token economy in Elementary level 3 at Ramkhamhaeng University Demonstration Schoolm and 2) to study student achievement before and after home economics and technology education when applying a reward program. The sample group were Elementary 3/2 and 3/3, in the first semester of the academic year 2018 in total of 62 persons. The research was conducted by using an experimental research model. The experimental period was 3 weeks, 2 periods (50 minutes each) per week, totaling 6 periods. The research instruments were an achievement test, lesson plans, and a questionnaire for the opinions and feelings of students toward rewards receiving through answering questions and class participation. The questionnaire was a rating scale using analytic induction obtained from observation and the achievement measurement was analyzed by using mean and standard deviation. Achievement before and after learning were compared by using a t-test dependent. The results found that using a reward program to increase motivation resulted in students being more enthusiastic to study, more responsible and interested in participating in various activities has been arranged by the instructor. In addition, the learning achievement of the learners was higher than before learning at the statistical significance level of .05.